Homology Modeling of Predicted Methyl Transferases (STY 3264): A Protein of Salmonella TYPHI CT18 - Anila Farid, Beenish Haider, Kehkashan Akbar, Ammar Mehfooz, Ziyad Ahmad, Fazal E Raheem, Furqan Arshad, Bilal Saeed, Umair Aslam, Maheen, Irfan Ullah (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Salmonella typhi gives rise to typhoid fever which is life threatening illness.It puts end to approximately 600,000 people per annum around the world.Food and water are the leading components through which this disease is passed on and becomes origin of typhoid.It lays out widely where cleanliness is very substandard. Objective: To construct 3 dimensional structure of protein Methyl Transferase of Salmonella typhi CT18 by homology modeling. Materials and Methods: Bioinformatic tools and programs like Comprehensive Microbial Resource (CMR), Interproscan, Basic Local Alignment Search Tool (BLAST), Modellor 9.10, Procheck and Prosa were helpful for the complete homology modeling of methyl transferases (STY 3264).The models were visualized by DS Viever. Results: Homology modeling is an effective method to find structure of methyl transferase protein for future discovery of drugs. Conclusion: Homology modeling is an effective method to find structure of protein which provides good solution for drug discovery.